Promosi Budaya Republik Ceko Berbasis Keagamaan di SD dan SMP HKBP Sidorame Medan - Jojor - Silalahi; Bangun Munthe; Imelda Butar-butar; Nurliani Siregar; Janwar Tambunan; Bangun Aruan; Hendry Dj Simanullang; Sylvia Simanjuntak; Anggun Naibaho; David Guth; Dusan Jina; Martin Maděra; Matous Havrlik; Jan Tomasov; Lenka Křivánková; David Mrazek (Universitas Tanjungpura, 2022)
AbstractThe program of International Public Community Service is aimed to promote the culture of Czech Republic with religious basic. This activity was carried out by lecturers and students from the Christian Religion Education Study Program, Faculty of Teacher Training and Education, HKBP Nommensen University with students from Czech University. The implementation of the program on July 25-26, 2022. Nowdays, the secularization in Czech Republic is increased. Many people prefer not to make public their religious or spiritual identity . The reason is related to history of the nation. When the country was under communist tyranny, all religion organization was destroyed and the people was not allowed and persecuted when they expressed their faith publicly. By this program, the students have a good lesson which telling them that it is good to express our religious activities in peace, especially in Indonesian context with many religions. Keywords: Culture, Religion, Basic. Program Pengabdian Masyarakat Internasional ini bertujuan untuk mempromosikan budaya Republik Ceko berbasis keagamaan. Kegiatan ini dilakukan oleh dosen dan mahasiswa dari Program Studi Pendidikan Agama Kristen dengan mahasiswa dari Universitas Ceko. Pelaksanaan program dilakukan dari tanggal 25-26 Juli 2022. Saat ini, sekulerisasi di Republik Ceko meningkat. Banyak penduduk lebih memilih untuk menyembunyikan identitas agama mereka. Alasan mereka ini memiliki hubungan dengan sejarah bangsa mereka. Ketika bangsa Ceko di bawah tirani komunis Uni Soviet, mereka dilarang untuk mengekspresikan kegiatan keagamaan secara terbuka dan seluruh aktifitas organisasi keagamaan dirusak. Melalui program ini, siswa memperoleh pelajaran yang berharga bahwa adalah baik untuk mengekspresikan kehidupan keagamaan kita di tengah-tengah masyarakat secara damai, dalam konteks Indonesia yang majemuk. Kata Kunci : Budaya, Agama, Basis